Nutrition Education 4.0 to Prevent Overweight and Obesity Through Webinar: A Research Protocol - Mahmudiono, Trias; Atmaka, Dominikus Raditya; Loh, Su Peng; Rachmah, Qonita; Mahmudah, Mahmudah; Arini, Shintia Yunita; Vidianinggar, Mutiara Arsya; Wisnuwardani, Ratih Wirapuspita; Adhi, Kadek Tresna; Haryana, Nila Reswari; Wisnusanti, Setyo Utami; Indah, Windi; et al. (Scientific Foundation SPIROSKI, Skopje, Republic of Macedonia, 2022)
The COVID-19 pandemic in Indonesia has made changes in the learning system from face-to-face learning to online learning. With these conditions, technology should be utilized by making an innovation to improve the quality of learning. In this regard, innovations that can be done include the implementation of website seminar activities (webinar) in the midst of a pandemic. Webinars are a learning resource that can be widely accessed by students, academics, and the general public. Of course, this webinar activity is very useful to increase knowledge and insight. The prevalence of obesity in Indonesia according to Riskesdas 2018 shows that 13.6% of adults aged >18 years are overweight while 21.8% are obese. One of the challenges in this phase of life is how to influence and encourage young adults to adopt healthy eating behaviors. Therefore, one way that can be done to increase knowledge, attitudes, and behavior toward eating habits is to provide nutrition education through social media. This study aims to increase knowledge, attitudes, and behavior toward the habit of ordering food online, nutrient-dense food and energy-dense food, food safety, physical activity, sugar-sweetened beverage, and intake of energy, protein, fat, and fiber through the platform. Social media is widely used by the target. This is a randomized control trial study by giving nutrition education intervention related to reduction of obesity in adults age 17–25 years. This study targets adults using a quasi-experiment design with a pre- and post-test control group design. The study will be conducted online in Indonesia. A total of 311 adults aged 17–25 years are joining in this research.